2017
DOI: 10.1021/acs.jpclett.7b00275
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Two-Dimensional Phase of Boron with Anisotropic Electric Conductivity

Abstract: Two-dimensional (2D) phases of boron are rare and unique. Here we report a new 2D all-boron phase (named the π phase) that can be grown on a W(110) surface. The π phase, composed of four-membered rings and six-membered rings filled with an additional B atom, is predicted to be the most stable on this support. It is characterized by an outstanding stability upon exfoliation off of the W surface, and unusual electronic properties. The chemical bonding analysis reveals the metallic nature of this material, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…1 shows the band structure of both allotropes, computed within both DFT and the GW approximation. Our DFT calculations agree well with previous local and semi-local DFT studies in the features of the band structure; [12][13][14][15][16][17][18][20][21][22][23][24][25][26]41,55 we predict that both borophene allotropes are metallic but that their band structures differ substantially. For % , two bands cross the Fermi energy (E F ) at distinct locations in the Brillouin zone, with a noticeably wide gap of 4.3 eV in the band structure at G (k = 0), while the "# bandstructure displays many bands crossing E F .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…1 shows the band structure of both allotropes, computed within both DFT and the GW approximation. Our DFT calculations agree well with previous local and semi-local DFT studies in the features of the band structure; [12][13][14][15][16][17][18][20][21][22][23][24][25][26]41,55 we predict that both borophene allotropes are metallic but that their band structures differ substantially. For % , two bands cross the Fermi energy (E F ) at distinct locations in the Brillouin zone, with a noticeably wide gap of 4.3 eV in the band structure at G (k = 0), while the "# bandstructure displays many bands crossing E F .…”
Section: Resultssupporting
confidence: 89%
“…Two-dimensional (2D) boron or borophene is a recently synthesized 1-9 monolayer material predicted to exhibit novel thermal and optoelectronic properties, [10][11][12][13][14] that could complement other two-dimensional materials in creating new nanoelectronic devices. Borophene can exist in many different allotropes, all, while metallic, displaying distinct features of the band structure; [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and has been predicted to form Ohmic contacts with other 2D semiconductors, suggesting that it can be a tunable monolayer metal. 27 Additionally, several reports have predicted phonon-mediated superconductivity in borophene, [22][23][24][25][26] which is very sensitive to carrier doping and strain, 25,26 and extremely low lattice thermal conductivity 28 compared with carbon-based materials 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the chemical bonding pattern of the 2D‐B 4 P 2 sheet, the solid‐state adaptive natural density partitioning (SSAdNDP) algorithm was used . Previously it was shown that SSAdNDP is a powerful tool for analyzing chemical bonding in two‐dimensional periodic systems . A plane wave (PW) calculation was performed using 450 eV energy cut off with convergence threshold 10 −6 eV for total energy.…”
Section: Methodsmentioning
confidence: 99%
“…To date, the true ground state structure of the monolayer is not known. 22,25,27,[41][42][43][44] It is predicted that planar boron sheets form a triangular bonding configuration which is unstable due to an excess of electrons that occupy antibonding orbitals; 12,13 this structure can be stabilized by the introduction of vacancies, an example of which is shown for the "# structure in Figure 1a, or out-of-plane buckling as shown for the % structure in Figure 1b. Additionally, when borophene is grown on substrates, the lattice mismatch between the substrate lattice constant and the periodicity of the boron sheet, as well as charge transfer between boron and substrate, favor certain atomic configurations of boron atoms (boron allotropes) and rotation angles between boron and substrate (Moire patterns).…”
Section: Introductionmentioning
confidence: 99%